Dodatek za postrežbo in pomoč - Vuga, Tanja (Podjetje in delo, 2021)
The right to social security is recognised in international law (e.g. the Universal Declaration of Human Rights, Article 22, International Covenant on Economic, Cultural and Social Rights, Article 9, European Social Charter, Article 12) as a fundamental human right. It can be defined as the right to security of income provided by public social systems at the time of the most burdensome events in an individual's life. Age, disability and death of the insured are definitely counted among them. The article examines one of the rights that fall within the social security system, i.e. the right to an allowance for assistance and attendance, which is regulated by the Pension and Disability Insurance Act (ZPIZ-2). The beneficiaries of this allowance are exhaustively listed in the Act in two separate articles, i.e. Articles 99 and 100 of ZPIZ-2. The purpose of the allowance is to provide monetary assistance to specifically defined insured persons in order to help them better maintain their basic life functions and prevent them to be neglected in terms of personal hygiene. It is an inalienable personal right that can not be transferred to another and can not be inherited. Thus, only the testator's claim to the allowance for assistance and service shall be passed to the heir, but not the right to the allowance itself.
Keywords: active insured persons; aktivni zavarovanci; blindness; disabled person; dodatek za postrežbo in pomoč; immovable property; invalidi; nepokretnost; Pension and Disability Insurance Institute; pension beneficiary; podedljivost; service and assistance allowance; slabovidnost; slepota; tenability; uživalci pokojnine; visually impaired; Zavod za pokojninsko in invalidsko zavarovanje